Study of The Application of UAV Drone and Civil 3D Technology in Road Infrastrukcture Projects on Java Island - Mbuinga, Firda Oktaviana; Pradoto, Rani Gayatri Kusumawardhani (Jurnal Teknik Sipil, 2025)
In 2030 it is estimated that the number of construction projects will increase by 85%, to answer this challenge, the construction world is expected to apply construction technology, some of which are UAV Drones and Civil 3D. The purpose of this study is to obtain the level of application, benefits of application, and utilization of UAV Drone and Civil 3D technology as well as to identify inhibiting factors in applying these two technologies. Data collection was carried out using a questionnaire instrument, then the data processing in this study used descriptive statistical analysis. The results of the UAV Drone application rate are rarely applied, for its use it is more applied to the monitoring stage, namely monitoring project progress, while utilization that requires advanced image processing is rarely applied. The most influential benefit of UAV Drone is minimizing time. As for the level of application of Civil 3D, which is often applied, its use is most widely applied at the design stage to design and model roads, the benefits of application that are felt to be very influential are minimizing time, increasing accuracy and efficiency, and reducing errors. From the resulting cartesian diagram, these two technologies are already in quadrant III (promoting) for UAV Drones and quadrant IV (highly implementation) for Civil 3D, so it is hoped that the authorities can make regulations or standards that can be used as a basis/reference in implementing (Infrastructure Building Information Modelling) I-BIM, especially in road infrastructure.